Do cacti form soil seed banks? An evaluation using species from the Southern Central Andes - Lindow López, Lucía Teresa (2018)
There is controversy over whether cactus species form soil seed banks. Although it is commonly assumed that cacti do not form seed banks, very few studies have evaluated them. In this work, we analysed whether cactus species form soil seed banks, studying seed distribution, seed density and seed longevity in the Southern Central Andes. Soil samples were collected in two microhabitats (under nurse plants and in bare areas) at 12 selected sites. We determined seed presence–absence, density and distribution for 32 native cactus species. Seed longevity for six of these species was determined through a burial experiment. We recorded viable seeds for 62.5% of the 32 evaluated species, finding variation in seed density between microenvironments and among populations. In some species, the highest seed density was found under potential nurse plants. Seed germination and seed viability decreased with burial time, with seed longevity always being <24 months after burial. Our results show strong evidence that cactus species do form seed banks. Seed density can vary between microenvironments and among populations, suggesting that cactus–nurse plant associations can also be explained by differential seed dispersal and not only by differential establishment. We found that Echinopsis and Gymnocalycium species form short-term seed banks. Our results will help to better understand the population dynamics of cactus species, a focal species group for conservation actions because many of them are threatened by human activities.